Motorisation of Chinese cities: pathways of sustainable urban mobility - Gao, Yuan (Curtin University, 2016)
China’s rapid urban motorisation has resulted from strong economic growth, rapid urban development and the prosperity of the Chinese automobile industry. However, Chinese urban fabrics, featuring traditional dense linear forms and mixed land use, favour walking, cycling and mass transit systems over automobiles. Chinese megacities like Beijing and Shanghai reached peak car use from 2010 in terms of modal split by daily trips. They are moving towards more sustainable urban forms built along dense corridors.